2012
DOI: 10.1007/s11250-012-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Fattening performance, carcass and meat quality characteristics of Kivircik male lambs

Abstract: The objective of this study was to determine the fattening performance and carcass and meat quality characteristics of Kivircik twin male lambs. Twelve lambs at approximately 5 months of age were subjected to a finishing diet for 60 days. Average live weight of lambs at the beginning and the end of the fattening were 23.14 ± 0.84 and 39.0 ± 1.01 kg, respectively. Daily live weight gain and feed conversion efficiency were found as 0.265 ± 0.007 and 6.14 kg, respectively. Hot carcass weight, cold carcass weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
7
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
7
7
3
3
Order By: Relevance
“…These characteristics of Karayaka male lambs in the present study were within the normal range (Olfaz et al 2005;Sen et al 2011;Sirin et al 2011) and were also found to be comparable to the native sheep breeds such as Bafra (Yakan & Unal 2010), Awassi, Morkaraman (Esenbuga et al 2009) and Kivircik (Gökdal et al 2012) of Turkey. Although the BtW and FS have an impact upon slaughter weight, carcass weight and meat quality (Sañudo et al 1998), the situation in the present study may be explained by the fact that the BW at the start of the fattening and the feed ingredients of the TMR and FCF were similar and the number of replicates per treatment was comparatively low.…”
Section: Resultssupporting
confidence: 86%
“…These characteristics of Karayaka male lambs in the present study were within the normal range (Olfaz et al 2005;Sen et al 2011;Sirin et al 2011) and were also found to be comparable to the native sheep breeds such as Bafra (Yakan & Unal 2010), Awassi, Morkaraman (Esenbuga et al 2009) and Kivircik (Gökdal et al 2012) of Turkey. Although the BtW and FS have an impact upon slaughter weight, carcass weight and meat quality (Sañudo et al 1998), the situation in the present study may be explained by the fact that the BW at the start of the fattening and the feed ingredients of the TMR and FCF were similar and the number of replicates per treatment was comparatively low.…”
Section: Resultssupporting
confidence: 86%
“…They can directly reflect the body composition proportions of the edible parts. Studies have reported that slaughter rates trend upward as LWBS increases (Gökdal, Atay, Eren, & Demircioğlu, ; Hawkins et al, ; Sen, Sirin, Ulutas, & Kuran, ). This experiment had results consistent with those found above.…”
Section: Discussionmentioning
confidence: 99%
“…The water content of Muscle Longissimus dorsi was 76.9%, which according to Gökdal et al (2012) is in the normal range (70-80%).…”
Section: Discussionmentioning
confidence: 86%